Brand Image and Brand Attitude as Drivers of Brand Loyalty in Green Restaurants: A Study in Negeri Sembilan, Malaysia - Krishnan, Vijayaletchumy; Malek, Bahiah A; Mathews, Mary; Kanagasingam, Kalaveny; Nusraningrum, Dewi (Journal of Ecohumanism, 2024)
This study explores the relationship between brand image, brand attitude, and brand loyalty in the context of green restaurants in Negeri Sembilan, Malaysia. Using a survey with validated scales, the research highlights that a strong and favorable brand image significantly enhances customer attitudes towards green restaurants, which in turn drives brand loyalty. The study also identifies brand attitude as a mediator in this relationship, emphasizing its role in converting a positive brand image into increased customer loyalty. The findings underscore the importance of not only establishing a positive brand image but also fostering favorable customer attitudes to build lasting loyalty. These insights offer valuable guidance for green restaurant operators seeking to leverage brand management strategies to strengthen customer engagement and loyalty in the sustainable dining sector.